Primary Presentation of Systemic Lupus Erythematosus with Pulmonary Embolism: A Case Report - Naima Fellak; Kareem Kamil Mohamed; Hussein Saleh (South Eastern European Journal of Public Health, 2024)
Pulmonary embolism (PE) as the first clinical manifestation of systemic lupus erythematosus (SLE) is an unusual and rare presentation. This case report discusses a 30-year-old male who presented with chest pain and hypoxemia at a hospital in Dubai. Initial workup revealed elevated D-dimer levels and a positive CT pulmonary angiogram confirming PE. The patient’s medical history was unremarkable, except for a recent transient leg discomfort. Upon further investigation, hypoalbuminemia and proteinuria suggested nephrotic syndrome. A thorough autoimmune evaluation revealed elevated anti-dsDNA antibodies, leading to a diagnosis of SLE nephritis. This case emphasizes the necessity of considering SLE as a differential diagnosis for young patients with unexplained thrombotic events, even in the absence of traditional SLE symptoms. Treatment and early recognition are important in managing thrombotic complications in SLE.